2006
DOI: 10.1002/humu.20387
|View full text |Cite
|
Sign up to set email alerts
|

Acute myelogenous leukemia–derivedSMAD4 mutations target the protein to ubiquitin-proteasome degradation

Abstract: Disruption of transforming growth factor-beta (TGFB1/TGF-beta) signaling contributes to the formation of human hematological malignancies. Smad4, a tumor suppressor, functions as an essential intracellular signal transducer of the TGF-beta signaling pathway. Recent studies have demonstrated that some tumor-derived mutations of Smad4 are associated with protein instability; however, the precise mechanism by which mutated Smad4 proteins undergo rapid degradation remains to be elucidated. A missense mutation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…83 Nevertheless,a number of cases have been reported involving SMAD4 and TGFBR2 in patients with acute myelogenous leukemia (AML). [84][85][86][87] For example, in a study investigating human AML genomes, various copy number alterations were found recurrently modified, 1 of which represented the deletion of SMAD4.…”
Section: Leukemiamentioning
confidence: 99%
“…83 Nevertheless,a number of cases have been reported involving SMAD4 and TGFBR2 in patients with acute myelogenous leukemia (AML). [84][85][86][87] For example, in a study investigating human AML genomes, various copy number alterations were found recurrently modified, 1 of which represented the deletion of SMAD4.…”
Section: Leukemiamentioning
confidence: 99%
“…[87][88][89][90] Using ultra-dense array comparative genomic hybridization on 86 AML genomes, 18 copy number alterations regions were found recurrently modified, one of which represented the deletion of the SMAD4 gene, demonstrating that SMAD4 can be an AMLassociated gene (Walter, PNAS, 2009). Furthermore, sporadic mutations in both TbRI and TbRII have been reported in lymphoid neoplasms.…”
Section: Spotlightmentioning
confidence: 99%
“…15 A relation between aberrations in the TGF-␤-signaling pathway and acute myelogeneous leukemia (AML) has also been reported. [16][17][18] miRNAs are increasingly acknowledged as important regulators of translation and hence protein synthesis. miRNAs are Submitted March 11, 2011; accepted October 8, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…15 A relation between aberrations in the TGF-␤-signaling pathway and acute myelogeneous leukemia (AML) has also been reported. [16][17][18] miRNAs are increasingly acknowledged as important regulators of translation and hence protein synthesis. miRNAs are 19-25 nucleotide noncoding RNA molecules that can regulate gene expression posttranscriptionally by binding to partially complementary sequences, mainly in the 3Ј-untranslated region (3Ј-UTR) of their target mRNA.…”
Section: Introductionmentioning
confidence: 99%